Carbon nanotube fiber film reinforced ceramic matrix composite material and preparation method thereof

By using carbon nanotube fiber film reinforcement in ultra-high temperature ceramic matrix composite materials, combined with multi-layer structure and specific process processing, the problems of poor thermal shock resistance and insufficient thermal conductivity of traditional materials under high temperature conditions are solved, and efficient heat dissipation and thermal stress relief of the materials are achieved, which significantly improves its mechanical and thermal performance.

CN119899040APending Publication Date: 2025-04-29SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510102964.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing ultra-high temperature ceramic matrix composite materials have poor thermal shock resistance and severe wire breakage under high temperature conditions, and the thermal conductivity of carbon fibers is limited, making it difficult to meet the needs of rapid heat dissipation and thermal stress relief.

Method used

The carbon nanotube fiber film is used as the reinforcement body, and a carbon nanotube fiber film reinforced ceramic matrix composite material with excellent unidirectional properties is prepared by combining a multi-layer stacking structure, a pyrolytic carbon interface layer and a ceramic layer, combined with floating catalytic chemical vapor deposition method, a pyrolytic deposition, impregnation-laminated molding process and sintering treatment.

Benefits of technology

It significantly improves the fracture toughness and bending strength of the composite material, improves thermal shock resistance and high temperature stability, and has excellent thermal conductivity and heat resistance, which is suitable for extreme environmental applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899040A_ABST
    Figure CN119899040A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube fiber film reinforced ceramic matrix composite material and a preparation method thereof. The composite material comprises a carbon nanotube fiber film, a pyrolytic carbon interface layer and a ceramic layer, the pyrolytic carbon interface layer comprises a first surface and a second surface, the first surface is tightly combined with the carbon nanotube fiber film, and the second surface is tightly combined with the ceramic layer. The fracture toughness and bending strength of the composite material are remarkably improved, and the problem that a traditional ceramic material is high in brittleness is solved; through dipping and lamination mould pressing processes, the dispersity of the carbon nanotube fiber film in a ceramic matrix is effectively controlled, the problem of uneven distribution of traditional reinforcements is avoided, and meanwhile, the overall structure of the composite material is compact and stable; the material has excellent thermal protection performance, also has good thermal conductivity and heat resistance, can maintain excellent mechanical properties in a high-temperature environment, and is suitable for application in an extreme environment; the preparation process is relatively simple, the operability is high, and large-scale production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a carbon nanotube fiber film reinforced ceramic matrix composite material and a preparation method thereof. Background Art

[0002] Ultra-high temperature ceramic matrix composites are widely used in extreme environments such as aerospace, hypersonic aircraft and engine protection due to their excellent high-temperature mechanical properties, oxidation resistance and thermal stability. However, the current mainstream ultra-high temperature ceramic matrix composites usually use carbon fiber fabrics as reinforcement phases. Such materials are prone to poor thermal shock resistance and severe wire breakage under high temperature conditions. In addition, the thermal conductivity of carbon fiber is limited, which makes it difficult to meet the material's needs for rapid heat dissipation and thermal stress relief in ultra-high temperature environments, limiting the further development of the material. In recent years, two-dimensional composite film materials have been considered to be an important direction for breaking through the performance bottleneck of traditional ceramic matrix composites due to their flexibility, high thermal conductivity and thermal expansion coordination. This material significantly improves thermal shock resistance and high-temperature stability through a two-dimensional reinforcement structure. However, the current composite materials based on carbon fiber fabrics still have problems such as weakened interface bonding and thermal expansion mismatch in high-temperature dynamic environments, and cannot fully meet actual needs.

[0003] Carbon nanotubes have been proven to be a very promising reinforcement material due to their ultra-high thermal conductivity, excellent mechanical properties and good antioxidant ability. The carbon nanotube fiber film is a unidirectional fiber film made by winding wet carbon nanotube fibers. It has high strength, high toughness and excellent thermal and electrical conductivity in the fiber direction. This film has a multi-scale reinforcement effect. It not only retains the excellent properties of carbon nanotubes, but also shows extremely high flexibility and processability. It is suitable for the reinforcement structure of ultra-high temperature ceramic-based carbon composite materials.

[0004] At present, some literature and patents have studied ultra-high temperature ceramic matrix composites based on carbon fiber reinforcement. For example, a study (Corrosion Science, 88 (2014) 49–55) showed that by reinforcing SiC-ZrC ceramic matrix composites with carbon fiber fabrics, the material can maintain good ablation resistance at 3723 K. Another patent (CN106218061 A) uses carbon fiber fabrics to prepare two-dimensional reinforced ceramic matrix composites. Although the tensile strength of the composite material is improved to a certain extent, the overall performance is still difficult to meet the requirements of high temperature and complex working conditions due to the problem of carbon fiber fracture in extreme environments. In contrast, carbon nanotube fiber film provides a new solution for the design of ultra-high temperature ceramic matrix composites with its high thermal conductivity, excellent mechanical properties and structural flexibility. However, the current research on carbon nanotube fiber film reinforced ceramic matrix composites is still in the exploratory stage, and there are still significant challenges in the precise control of composite components (content and distribution), interface bonding mechanism and preparation process. Therefore, developing an efficient preparation process for carbon nanotube fiber film reinforced ceramic-based composites is not only of great significance for improving the performance of ceramic-based composites, but also provides new technical support for promoting their engineering development in high-performance application fields. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a carbon nanotube fiber film reinforced ceramic matrix composite material and a preparation method thereof.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: In a first aspect, the present invention provides a carbon nanotube fiber film reinforced ceramic matrix composite material, which comprises a multi-layer stacked carbon nanotube fiber film, a pyrolytic carbon interface layer and a ceramic layer; The pyrolytic carbon interface layer comprises a first surface and a second surface, wherein the first surface is tightly combined with the carbon nanotube fiber film, and the second surface is tightly combined with the ceramic layer.

[0007] In a second aspect, the present invention further provides a method for preparing the above-mentioned carbon nanotube fiber film reinforced ceramic matrix composite material, which comprises: Providing carbon nanotube fiber films; Forming a pyrolytic carbon interface layer on the surface of the carbon nanotube fiber film by pyrolytic deposition to obtain a first assembly; The first assembly is contacted and infiltrated with a ceramic precursor solution so that the ceramic precursor solution is adsorbed on the first assembly to obtain a second assembly; performing a stacking and hot pressing process on a plurality of the second assemblies to form a third assembly; The third assembly is sintered to convert the ceramic precursor into a ceramic material, thereby obtaining a carbon nanotube fiber film reinforced ceramic matrix composite material.

[0008] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include: 1. The present invention provides a carbon nanotube fiber film reinforced ceramic-based composite material and a preparation method thereof. A carbon nanotube fiber film with excellent unidirectional properties is prepared by a floating catalytic chemical vapor deposition method, which significantly improves the fracture toughness and bending strength of the composite material and solves the problem of high brittleness of traditional ceramic materials.

[0009] 2. The present invention provides a carbon nanotube fiber film reinforced ceramic-based composite material and a preparation method thereof. Through the impregnation and lamination molding process, the dispersion of the carbon nanotube fiber film in the ceramic matrix is ​​effectively controlled, avoiding the problem of uneven distribution of traditional reinforcements. At the same time, the overall structure of the composite material is dense and stable.

[0010] 3. The present invention provides a carbon nanotube fiber film reinforced ceramic matrix composite material and a preparation method thereof. A pyrolytic carbon interface layer is prepared by chemical vapor deposition, and then a layered carbon nanotube fiber film reinforced ceramic matrix composite material is successfully prepared through an impregnation-laminate molding curing-hot pressing sintering method. The material has excellent thermal protection performance, good thermal conductivity and heat resistance, can maintain excellent mechanical properties under high temperature environment, and is suitable for applications in extreme environments.

[0011] 4. The preparation process provided by the present invention is relatively simple, highly operable, easy to achieve large-scale production, and has broad application prospects. It can be widely used in the fields of aerospace and high-temperature structural parts, and has important industrial value and promotion potential.

[0012] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a side morphology photograph of a carbon nanotube fiber film reinforced ceramic matrix composite material before sintering provided in a typical embodiment of the present invention; Figure 2 This is a physical photo of a carbon nanotube fiber film reinforced ceramic matrix composite material provided by a typical implementation example of the present invention; Figure 3 This is a SEM photo of a pyrolytic carbon layer prepared by a CVD method provided in a typical embodiment of the present invention; Figure 4This is a cross-sectional SEM photograph of a carbon nanotube fiber film reinforced ceramic matrix composite material provided in a typical embodiment of the present invention; Figure 5 is a surface SEM photograph of a carbon nanotube fiber film (RAW) provided in a typical embodiment of the present invention; Figure 6 This is a surface SEM photograph of a carbon nanotube fiber film (RAW+PyC) deposited on the interface of pyrolytic carbon provided by a typical embodiment of the present invention; Figure 7 This is a surface SEM photograph of a carbon nanotube fiber film reinforced ceramic matrix composite material (RAW+PyC+C) provided in a typical implementation case of the present invention. DETAILED DESCRIPTION

[0014] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0015] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0016] The embodiment of the present invention provides a carbon nanotube fiber film reinforced ceramic matrix composite material, which includes a multi-layer stacked carbon nanotube fiber film, a pyrolytic carbon interface layer and a ceramic layer; The pyrolytic carbon interface layer comprises a first surface and a second surface, wherein the first surface is tightly combined with the carbon nanotube fiber film, and the second surface is tightly combined with the ceramic layer.

[0017] As a typical example, the carbon nanotube fiber film reinforced ceramic matrix composite material provided by the present invention has a multilayer repetitive structure of carbon nanotube fiber film layer (having a pyrolytic carbon interface layer on the surface)-ceramic layer-film layer (having a pyrolytic carbon interface layer on the surface).

[0018] In some embodiments, the carbon nanotube fiber film has a thickness of 20-40 μm.

[0019] In some embodiments, the pyrolytic carbon interface layer has a thickness of 300 nm to 1 μm.

[0020] In some embodiments, the ceramic layer has a thickness of 5-50 μm.

[0021] In some embodiments, the material of the ceramic layer includes any one of carbide, boride, oxide, and nitride, or a combination of two or more thereof.

[0022] In some embodiments, the material of the ceramic layer includes at least carbide. In the above technical solution, the material selection of the ceramic layer can be multiple, but in the preferred solution, at least carbide is selected. This is because, during the hot pressing and sintering process of the carbide-containing ceramic layer (the corresponding precursor material contains carbon elements), the carbon elements in the ceramic precursor and the pyrolytic carbon layer can undergo carbon diffusion bonding to form a strong interface effect, thereby enhancing the thermal conductivity, toughness and strength and other properties, and it is also beneficial to connect the multilayer material into a whole. On the other hand, carbide ceramics themselves have excellent high-temperature stability and antioxidant ability, which greatly maintains the performance of carbon nanotube fiber films in extreme temperature environments. At the same time, carbide ceramics also have good thermal conductivity. Good interlayer thermal conductivity enhances the overall thermal management capability of the composite material under ultra-high temperature ablation, enhances the heat dissipation capability, and slows down the accumulation of local high temperatures, thereby avoiding the degradation of material properties or structural damage due to excessive temperature. The embodiment of the present invention further provides a method for preparing the carbon nanotube fiber film reinforced ceramic matrix composite material provided by any of the above embodiments, which comprises the following steps: Providing carbon nanotube fiber films; Forming a pyrolytic carbon interface layer on the surface of the carbon nanotube fiber film by pyrolytic deposition to obtain a first assembly; The first assembly is contacted and infiltrated with a ceramic precursor solution so that the ceramic precursor solution is adsorbed on the first assembly to obtain a second assembly; performing a stacking and hot pressing process on a plurality of the second assemblies to form a third assembly; The third assembly is sintered to convert the ceramic precursor into a ceramic material, thereby obtaining a carbon nanotube fiber film reinforced ceramic matrix composite material.

[0023] In some embodiments, the preparation method may further include the following steps: After the sintering treatment, the obtained carbon nanotube fiber film reinforced ceramic matrix composite material is subjected to a secondary infiltration and secondary sintering process with a ceramic precursor solution under vacuum conditions for multiple rounds to densify the carbon nanotube fiber film reinforced ceramic matrix composite material.

[0024] In some embodiments, the specific method for preparing the carbon nanotube fiber film may include: A floating vapor deposition method is used to form a carbon nanotube aerogel, and the carbon nanotube aerogel is rolled into a film and brought into contact with a liquid to achieve densification, thereby obtaining a densified wet film; Under the continuous action of the pulling force, the densified wet film is dried to obtain the carbon nanotube fiber film.

[0025] Regarding the contact wetting conditions, in some embodiments, the mass fraction of the ceramic precursor in the ceramic precursor solution is 5-60%.

[0026] In some embodiments, the ceramic precursor includes any one or a combination of two or more of polycarbosilane, polyzirconocarbosilane, polysiloxane, polydimethylsiloxane, and polyborosilazane; In some embodiments, the contact and immersion time between the first assembly and the ceramic precursor solution is more than 20 minutes.

[0027] Regarding the hot pressing treatment, in some embodiments, the stacking hot pressing treatment specifically includes: stacking a plurality of the first assemblies in a thickness direction to form a stack; The temperature is gradually raised to the preset temperature at the set pressure, and the preset temperature is maintained for a set time; The heating time to the preset temperature is 2-5 h, the setting time is 1-3 h, the target temperature is 180-220 °C, and the setting pressure is 0.5-1 MPa.

[0028] Finally, regarding the preferred conditions for the sintering treatment, in some embodiments, the sintering treatment is carried out in a protective atmosphere, the sintering temperature is 1100-1500°C, the sintering time is 2-3 h, and the heating and cooling rate is 1-2°C / min.

[0029] As some typical application examples of the above technical solutions, the specific process flow of the preparation method provided by the embodiment of the present invention can be: S1. The carbon nanotube fiber precursor (generally in aerogel state) prepared by floating catalytic chemical vapor deposition (FCCVD) is directly collected onto a roller of a certain diameter and length, and then removed, dried and molded to obtain a carbon nanotube fiber film.

[0030] In step S1, the carbon nanotube fiber film prepared by floating catalytic chemical vapor deposition has different thicknesses due to the difference in winding rate and winding time during the preparation process. The preferred winding rate of the carbon nanotube fiber is 10-20 m / s, and the winding time is 15-25 min. The composition of the carbon nanotube fiber film is at least any one of double-walled or multi-walled carbon nanotubes. After the wet film is removed, the two ends of the film are clamped with a mountain clamp, and an object of 25-50 g is hung to improve the orientation degree of the film during the drying process (50-100°C).

[0031] The use of floating catalytic chemical vapor deposition (FCCVD) to prepare carbon nanotube fibers and directly winding wet fibers to form carbon nanotube fiber films has significant advantages. First, wet fibers have good flexibility and ductility, which facilitates uniform winding. At the same time, the boundaries between wet fibers are not obvious and are easy to fuse together, thus easily forming a film with a highly regular structure. Secondly, the FCCVD method can achieve continuous preparation of carbon nanotube fibers, which can greatly improve the efficiency of film preparation and achieve large-scale production. In addition, the parameters of this process are controllable, and it is easy to prepare carbon nanotube fiber films with uniform parameters to ensure the consistency of the material. At the same time, the fibers are tightly bonded during the wet winding process, and the density and uniformity of the film are significantly improved, providing a good reinforcement material for the preparation of composite materials.

[0032] Of course, the specific process may be different from the above exemplary method, and various other methods may be used to obtain carbon nanotube fiber films with similar properties to achieve similar purposes.

[0033] S2. Uniformly depositing an amorphous carbon interface layer of a certain thickness on the surface of the carbon nanotube fiber film by chemical vapor deposition (CVD).

[0034] In step S2, the temperature and time of chemical vapor deposition are controlled so that the thickness of the prepared pyrolytic carbon layer is within a certain range. Specifically, under a protective atmosphere (argon or nitrogen, with a flow rate of 100-500 sccm), the CVD furnace is heated to a temperature of 1000-1300 °C, 30-300 sccm of hydrogen is first introduced, the protective atmosphere and the hydrogen input are kept unchanged, and then a certain flow of carbon source (the ratio of carbon source concentration to hydrogen concentration is 0.5-0.9) is introduced, and after maintaining for 10-200 min, the carbon source is first stopped and then the hydrogen is stopped, and then air-cooled or cooled at a rate of 2-10 °C / min. The carbon source is methane, ethane, propane, ethylene and propylene, and the thickness of the pyrolytic carbon layer is 500 nm-1μm.

[0035] S3. Cutting the carbon nanotube fiber film with an amorphous carbon interface layer into specified dimensions (length and width) using a laser.

[0036] S4. Soak a certain number of carbon nanotube fiber films in a ceramic precursor solution and maintain the solution for a period of time to ensure that the front and back sides of each film are in contact with the ceramic precursor solution.

[0037] In step S4, the types of ceramic precursors and solvents are various, but the mass fraction of the ceramic precursor in the solution needs to be controlled within a certain range. At the same time, in order to obtain a uniform ceramic precursor solution, the solution is usually subjected to ultrasonic treatment for a certain period of time. The preferred mass fraction of the ceramic precursor in the ceramic precursor solution is 5-60 wt%, and the ultrasonic treatment time of the solution is 1-2 h. The solvent is mostly an organic solvent, such as ethanol, isopropanol, methanol, acetone, methyl ethyl ketone, ethyl acetate, methyl formate, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the ceramic precursor includes some polymer precursors, such as polycarbosilane (PCS), polyzirconium carbosilane (PZCS), polysiloxane (PSZ), polydimethylsiloxane (PDMS), polyborosilazane (PBSZ) At least one of the following. In order to ensure that both sides of the carbon nanotube fiber film are evenly coated with the ceramic precursor solution, the film should be suspended in the ceramic precursor solution and soaked for a period of time, and should be taken out vertically when taken out. The preferred soaking time is 20 min-3 h.

[0038] S5. Take out the soaked carbon nanotube fiber film, lay it out in a certain direction and put it into a mold, select appropriate curing temperature and pressure, hot-press cure the ceramic precursor and evaporate the solvent, so that the multi-layer carbon nanotube fiber film soaked in the ceramic precursor becomes a whole.

[0039] In step S5, the solvent of the ceramic precursor solution is slowly volatilized by the synchronous action of the gradient temperature program and the pressure to prevent the carbon nanotube fiber film from being distorted and deformed due to the stress caused by the solvent volatilization. Then, the target temperature and a certain pressure are maintained for a period of time, and the ceramic precursor is gradually solidified, and finally merged with the carbon nanotube fiber film into a whole. The preferred gradient temperature program is 50℃ (30 min)-80℃ (30 min)-120℃ (30 min)-150℃ (30 min)-180℃ (3 h), the pressure is 0.5-1 MPa, the curing temperature is 180℃, the curing time is 3 h, and the pressure is 1 MPa. S6, the cured carbon nanotube fiber film is placed in a tubular furnace for sintering, and the sintering temperature and the temperature rise and fall time are controlled to obtain a carbon nanotube fiber film reinforced ceramic matrix composite material.

[0040] In step S6, the sintering atmosphere, heating rate, sintering time and sintering temperature of the tube furnace sintering are controlled, and the interlayer ceramic phase and the film of the carbon nanotube fiber film reinforced ceramic matrix composite material should be closely attached. The preferred sintering atmosphere is nitrogen and argon atmosphere, the heating rate is 1-2°C / min, the sintering time is 2-3 hours, and the sintering temperature is 1100-1500°C.

[0041] S7. Repeatedly introduce ceramic precursors to fill the pores through a vacuum impregnation method, and then solidify and sinter to make the surface of the composite material denser.

[0042] In step S7, the prepared carbon nanotube fiber film reinforced ceramic matrix composite material can be placed in a vacuum impregnation machine for vacuum impregnation, maintaining a vacuum degree of -0.1 MPa and impregnating for 30-180 min, and then solidifying and sintering, and repeating this process to achieve densification of the composite material.

[0043] Based on the above technical solution, the present invention has developed an ultra-high temperature ceramic-based composite material reinforced with a carbon nanotube fiber film. By optimizing the interface bonding technology between the carbon nanotube fiber film and the ceramic matrix and adopting a laminated sintering process, the uniformity and density of the material are significantly improved. The composite material exhibits unique advantages in the following aspects: in terms of thermal conductivity and oxidation resistance, the carbon nanotube fiber film constructs an efficient heat conduction network, and the oxidation resistance is significantly enhanced. In terms of flexibility and versatility, the film structure gives the material a certain flexibility, adapts to complex high-temperature dynamic environments, and expands its application scenarios.

[0044] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0045] Example 1 In this embodiment, the preparation of the carbon nanotube fiber film reinforced ceramic matrix composite material includes the following steps. The main steps are: preparing a wet carbon nanotube fiber film by FCCVD, obtaining a carbon nanotube fiber film by drying and molding, and then obtaining the final composite material by the method of impregnation-lamination-molding curing-hot pressing sintering. The actual picture of the material before and after sintering is as follows: Figure 1 and Figure 2 shown.

[0046] (1) A wet carbon nanotube fiber film is prepared by floating catalytic chemical vapor deposition, the winding rate is controlled between 15-20 m / s, the winding time is 15-30 min, and the carbon nanotube fiber film has a uniform thickness. After the wet film is removed with a knife, the film is placed in an 80 ℃ oven to dry while ensuring that the film is stressed in the fiber direction.

[0047] (2) Place the obtained carbon nanotube fiber film on a customized quartz frame and put it into the highest temperature zone of the CVD furnace. Close the flange and introduce argon. Heat the CVD furnace to 1100 °C. First introduce hydrogen, keep the protective atmosphere and hydrogen input unchanged, then introduce ethylene. After maintaining for 30 min, stop introducing the carbon source first and then stop introducing hydrogen, and then air cool to room temperature. The thickness of the pyrolysis carbon layer is about 1 μm, and the following is obtained: Figure 3Materials shown.

[0048] (3) Use a laser marking machine to cut the carbon nanotube fiber film with an amorphous carbon interface layer into a specific size (slightly smaller than the cavity size of the customized graphite mold).

[0049] (4) First, the block of polycarbosilane is packaged in a sealed bag, and then crushed and ground into powder. 40 g is taken, and then 160 g of xylene is taken and the polycarbosilane powder is added to the xylene. The bag is sealed and then ultrasonically treated to obtain a 20 wt% silicon carbide ceramic precursor solution.

[0050] (5) Fix the carbon nanotube fiber film so that it is suspended in the ceramic precursor solution and soaked for a period of time.

[0051] (6) The immersed carbon nanotube fiber film is taken out and laid out in a uniform direction and placed in a self-made graphite mold. The solvent of the ceramic precursor solution is slowly evaporated through the synchronous action of a gradient temperature program and pressure to prevent the carbon nanotube fiber film from being distorted and deformed due to the stress caused by solvent evaporation. The temperature program is 50 ℃ (30 min) -80 ℃ (30 min) -120 ℃ (30 min) -150 ℃ (30 min) -180 ℃ (3 h), and the pressure is 1 MPa. Then, it is maintained at 180-220 ℃ and 1 MPa for 2-3 h. The ceramic precursor is gradually solidified and finally merged with the carbon nanotube fiber film into a whole.

[0052] (7) In a tubular furnace, under an argon atmosphere, the heating rate is 1-2 °C / min, the temperature is raised to 1500 °C, and the sintering time is 2 h. The interlayer ceramic phase of the carbon nanotube fiber film reinforced ceramic matrix composite material is closely attached to the film. The cross-sectional structure of the obtained material is as follows: Figure 4 As shown, and from Figure 4 It can be found from the corresponding element MAP diagram that carbon and silicon elements are distributed in layers, corresponding to the cross-sectional structure, but the carbon element is not completely concentrated in the carbon nanotube fiber film and the pyrolytic carbon layer, but has a gradient diffusion trend from the pyrolytic carbon layer to the ceramic layer, which indicates that the carbon element in the ceramic layer and the pyrolytic carbon layer undergo directional diffusion during the sintering process, which is beneficial to enhancing the interface bonding.

[0053] (8) The prepared carbon nanotube fiber film reinforced ceramic matrix composite material is placed in a vacuum impregnation machine for vacuum impregnation, the vacuum degree is maintained at -0.1 MPa and the impregnation is carried out for 2-3 hours, and then solidified and sintered. This process is repeated to achieve the densification of the composite material.

[0054] Characterize the surface of materials during the preparation of composite materials, such as Figure 5-Figure 7 As shown, Figure 5In the figure, RAW represents the original carbon nanotube fiber film, where the fiber-like aggregation can be clearly seen; Figure 6 The film surface after pyrolytic carbon treatment is shown, and relatively denser carbon deposition can be seen; Figure 7 The surface state of the final composite material is shown.

[0055] Example 2 This embodiment is substantially the same as Embodiment 1, except that only the mass percentage of the ceramic precursor solution is adjusted to 60 wt %.

[0056] High-concentration and low-concentration ceramic precursor solutions have significant differences in the sintering process and performance in the preparation of carbon nanotube fiber film reinforced ceramic matrix composites by lamination hot pressing. High-concentration precursor solutions can quickly form a dense ceramic matrix, improve hardness and compressive strength, while reducing sintering shrinkage and PIP times, thereby shortening the preparation process and saving costs, but may cause fluctuations in mechanical properties due to uneven ceramic distribution and residual pores.

[0057] The low concentration precursor solution is easier to distribute evenly, has less impact on the carbon nanotube fiber film, and enhances the toughness and tensile strength of the composite material, but the density of the ceramic matrix is ​​poor, the sintering shrinkage is large, and the hardness and compressive strength are reduced. The results show that the carbon nanotube fiber film reinforced ceramic matrix composite material prepared with this ratio has a higher ceramic content but increased brittleness under the same preparation times, and the size of the surface ceramic sheet is reduced. The reason is that the ceramic layer is too thick, which is more likely to produce large thermal stress and cracking during the sintering process. At the same time, its tensile strength is 100-200 MPa and its flexural strength is 200-400 MPa.

[0058] Example 3 The other conditions of this embodiment are the same as those of embodiment 1, except that the ceramic precursor solution is replaced with a polyzirconium carbosilane (PZCS) solution.

[0059] Different types of ceramic precursor solutions have a significant effect on the densification process and properties of carbon nanotube fiber film reinforced ceramic matrix composites prepared by lamination hot pressing. SiC in Examples 1 and 2 has excellent high temperature strength and oxidation resistance, but the sintering temperature is high, the interface bonding is weak, and the toughening effect is limited, while the main advantage of ZrC is that it has higher oxidation resistance.

[0060] Therefore, it is necessary to optimize the sintering process to improve the toughening properties of the composite material. The results show that the carbon nanotube fiber film reinforced ceramic matrix composite prepared by sintering the precursor has better ablation resistance, and its mass ablation rate measured by oxyacetylene ablation method is 1.1-3.4 mg / s.

[0061] Comparative Example 1 This comparative example is substantially the same as Example 1, except that: In the preparation process of the composite material, the part about the pyrolytic carbon layer is omitted, and the carbon nanotube fiber film is directly used for subsequent preparation, and other condition parameters and process steps remain unchanged.

[0062] This embodiment can still obtain a composite material with a multilayer structure and has obvious thermal protection performance, but the strength shows a downward trend, which is different from the composite material in Example 1.

[0063] Specifically reflected in: During the sintering stage, the ceramic layer will form bonds with the carbon on the surface of the carbon nanotube fiber film to enhance the adhesion of the ceramic layer on the film surface. During the ablation process, the composite material still maintains good ablation resistance. However, when the ceramic layer is in direct contact with the carbon nanotube fiber film, due to the loss of the protective effect of the pyrolytic carbon interface layer, the ceramic precursor will significantly etch the carbon nanotube fiber film during the sintering process, resulting in increased brittleness of the composite material and a decrease in tensile strength to 30-60 MPa. This reflects the important role of the pyrolytic carbon layer in the system.

[0064] Example 4 This embodiment is substantially the same as the first embodiment, the main difference being that the ceramic precursor is replaced with completely carbon-free polysiloxane, and the formed ceramic layer is made of silicon dioxide.

[0065] Its toughness and strength performance are significantly enhanced compared with the above-mentioned control example 1, but not as good as Example 1, and its tensile strength is 90-145 Mpa. The reasons are as follows. First, the interface bonding and formability of silicon carbide and carbon nanotube fiber film are better, and the precursor of the silicon dioxide ceramic layer does not contain carbon elements at all, and there is no phenomenon of carbon elements diffusing each other. The formed interface bonding performance is not as good as the implementation method of the precursor containing carbon elements in Example 1. Secondly, silicon carbide is a material with very high hardness, strength and wear resistance, and the mechanical properties of silicon dioxide are far inferior to silicon carbide. Finally, silicon carbide has a low thermal expansion coefficient, which is similar to that of carbon nanotube fiber film, reducing thermal stress in thermal cycles. The thermal expansion coefficient of silicon dioxide is higher, resulting in a higher degree of thermal expansion mismatch, which in turn generates more thermal stress at high temperatures or thermal cycles, affecting the performance of the composite material.

[0066] Furthermore, the inventors of the present invention have also tried a variety of ceramic layer precursors that do not contain carbon elements at all, and all of them performed similarly to Example 4, and were slightly inferior to Example 1 and other embodiments using carbon-containing ceramic precursors in terms of aspects related to interface performance.

[0067] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A carbon nanotube fiber film reinforced ceramic matrix composite material, characterized in that: It includes a multi-layer stacked carbon nanotube fiber film, a pyrolytic carbon interface layer and a ceramic layer; The pyrolytic carbon interface layer comprises a first surface and a second surface, wherein the first surface is tightly combined with the carbon nanotube fiber film, and the second surface is tightly combined with the ceramic layer.

2. The carbon nanotube fiber film reinforced ceramic matrix composite material according to claim 1, characterized in that: The thickness of the carbon nanotube fiber film is 20-40 μm; and / or, the thickness of the pyrolytic carbon interface layer is 300 nm-1 μm; And / or, the ceramic layer has a thickness of 5-50 μm.

3. The carbon nanotube fiber film reinforced ceramic matrix composite material according to claim 1, characterized in that: The material of the ceramic layer includes any one of carbide, boride, oxide, and nitride, or a combination of two or more thereof.

4. The carbon nanotube fiber film reinforced ceramic matrix composite material according to claim 3, characterized in that: The material of the ceramic layer at least includes carbide.

5. The method for preparing the carbon nanotube fiber film reinforced ceramic matrix composite material according to any one of claims 1 to 4, characterized in that: include: Providing carbon nanotube fiber films; Forming a pyrolytic carbon interface layer on the surface of the carbon nanotube fiber film by pyrolytic deposition to obtain a first assembly; The first assembly is contacted and infiltrated with a ceramic precursor solution so that the ceramic precursor solution is adsorbed on the first assembly to obtain a second assembly; performing a stacking and hot pressing process on a plurality of the second assemblies to form a third assembly; The third assembly is sintered to convert the ceramic precursor into a ceramic material, thereby obtaining a carbon nanotube fiber film reinforced ceramic matrix composite material.

6. The preparation method according to claim 5, characterized in that: Also includes: After the sintering treatment, the obtained carbon nanotube fiber film reinforced ceramic matrix composite material is subjected to a secondary infiltration and secondary sintering process with a ceramic precursor solution under vacuum conditions for multiple rounds to densify the carbon nanotube fiber film reinforced ceramic matrix composite material.

7. The preparation method according to claim 5, characterized in that: The method for preparing the carbon nanotube fiber film comprises: A floating vapor deposition method is used to form a carbon nanotube aerogel, and the carbon nanotube aerogel is rolled into a film and brought into contact with a liquid to achieve densification, thereby obtaining a densified wet film; Under the continuous action of the pulling force, the densified wet film is dried to obtain the carbon nanotube fiber film.

8. The preparation method according to claim 5, characterized in that: The mass fraction of the ceramic precursor in the ceramic precursor solution is 5-60%; And / or, the ceramic precursor includes any one or a combination of two or more of polycarbosilane, polyzirconocarbosilane, polysiloxane, polydimethylsiloxane, and polyborosilazane; And / or, the contact and infiltration time between the first assembly and the ceramic precursor solution is more than 20 minutes.

9. The preparation method according to claim 5, characterized in that: The stacking hot pressing process specifically includes: stacking a plurality of the first assemblies in a thickness direction to form a stack; The temperature is gradually raised to the preset temperature at the set pressure, and the preset temperature is maintained for a set time; The heating time to the preset temperature is 2-5 h, the setting time is 1-3 h, the target temperature is 180-220 °C, and the setting pressure is 0.5-1 MPa.

10. The preparation method according to claim 5, characterized in that: The sintering process is carried out in a protective atmosphere, the sintering temperature is 1100-1500°C, the sintering time is 2-3 h, and the heating and cooling rate is 1-2°C / min.

Citation Information

Patent Citations

  • Ceramic matrix composite material with double-layer structure and preparing method thereof

    CN106218061A